Carotenoids from persimmon juice processing. (March 2021) - Gea-Botella, S.; Agulló, L.; Martí, N.; Martínez-Madrid, M.C.; Lizama, V.; Martín-Bermudo, F.; Berná, G.; Saura, D.; Valero, M.
Graphical abstract: Highlights: Revalorization of by-products derived from industrialization of persimmon juice was approached. By-product B resulting from an enzymatic treatment was especially suitable for recovery carotenoids. Acetone extract from by-product B showed the largest amount of these pigments. β-cryptoxanthin and β-carotene represented 49.2% and 13.2% of total carotenoid content in the acetone extract. Total carotenoid content contributed greatly to antioxidant activity of persimmon by-product extract. Abstract: The aim of this study was the use and revalorization of two persimmon by-products A and B generated in the juice production process. The by-product B resulting from a pectinase enzymatic treatment of peels and pulp to optimize juice extraction was especially suitable for recovery of valuable bioactive carotenoids. The extraction solvents and solvent combinations used were: ethanol, acetone, ethanol/acetone (50:50 v/v) and ethanol/acetone/hexane (25:25:50 v/v/v). HPLC-DAD analysis detected and identified a total of nine individual carotenoids namely violaxanthin, neoxanthin, antheraxanthin, lutein, zeaxanthin, β-cryptoxanthin 5, 6-epoxide, β-cryptoxanthin, α-carotene, and β-carotene. β-cryptoxanthin and β-carotene represented 49.2% and 13.2% of the total carotenoid content (TCC) in the acetone extract from by-product B. TCC contributed greatly to antioxidant activity of acetone extract derived from this by-product. Pectinase enzymatic treatment of persimmon peels and pulp followed by absolute acetone extraction of carotenoids could be an efficient method to obtain a rich extract in these compounds that could be used as nutraceutical ingredient.